Petunjuk perencanaan tebal perkerasan lentur jalan raya dengan metode analisa komponen - [Tidak Terdaftar] ([Tidak Terdaftar], 1987)
Petunjuk perencanaan tebal perkerasan lentur jalan raya dengan metode analisa ...